Unemployment insurance in welfare states: Soft constraints and mild sanctions - Knud Røed; Lars Westlie (University of Oslo, Department of Economics, 2007)
Based on a sequence of reforms in the Norwegian unemployment insurance (UI) system, we show that activity-oriented UI regimes - i.e., regimes with a high likelihood of required participa-tion in active labor market programs, duration limitations on unconditional UI entitlements, and high sanction probabilities - deliver substantially shorter unemployment spells than pure income-insurance regimes. Soft constraints, in the form of activity requirements or small benefit cuts af-ter a pre-specified UI duration, have many of the same behavioral consequences as threats of complete benefit termination. Early introduction of a soft constraint appears particularly effec-tive; our results show that the expected unemployment duration falls by half a day for each week the soft constraint is moved ahead in the UI spell. Mild sanctions, in the form of temporary bene-fit terminations in response to inadequate search effort or excess choosiness, cause a significant rise in the job hazard.
Keywords: C14; C15; C41; J64; J65; J68; 330; Competing risks; unemployment insurance; timing-of-events; NPMLE; MMPH; Arbeitslosenversicherung; Arbeitsmarktpolitik; Arbeitsuche; Arbeitslosigkeit; Dauer; Norwegen